Surgical Treatment of Obesity. Special Mention to Roux-en-Y Gastric Bypass and Vertical Gastrectomy - Luesma, María José; Fernando, José; Cantarero, Irene; Lucea, Pilar; Santander, Sonia (Frontiers in Endocrinology, 2022)
Introduction: The prevalence of obesity has increased exponentially in recent decades, being one of the diseases that most affects global health. It is a chronic disease associated with multiple comorbidities, which lead to a decrease in life expectancy and quality of life. It requires a multidisciplinary approach by a specialized medical team. Obesity can be treated with conservative or with surgical treatments that will depend on the characteristics of the patient. Objective / Methodology: The referenced surgery can be performed using different surgical techniques that are analyzed in the present work through an exhaustive narrative bibliographic review in the PubMed and Cochrane databases, as well as in UpToDate. Results: Currently, those most used are restrictive techniques, specifically vertical gastrectomy and mixed techniques, with gastric bypass being the “gold standard”. Conclusions: In order to choose one technique or another, the characteristics of each patient and the experience of the surgical team must be taken into account.